Urban shrinkage in Halle, Germany: Research report, EU 7 FP project Shrink Smart (contract no. 225193), WP2 - Dieter Rink; Annegret Haase; Matthias Bernt; Thomas Arndt; Johanna Ludwig (Helmholtz-Zentrum für Umweltforschung (UFZ), 2011)
This report describes the process of shrinkage as it has occurred within the city of Halle. It examines the reasons, dynamics and patterns of change as well as the consequences for different fields of urban development and planning. The period covered in the report runs from the 1980s to the present day; in particular cases, longer or shorter time periods are considered. While Halle's new part, Halle-Neustadt, saw a rapid growth of population during the 1960s and 1970s, the old city of Halle underwent population losses throughout the whole time of the GDR. During the 1980s, both parts (at that time two different cities in administrative terms) were stagnating, the old parts of the city suffered from decay. Since 1990, Halle (including Halle-Neustadt) has seen a continuous and rapid process of population loss that hit the city after the systemic change and German reunification. Today, Halle still represents a shrinking city and expects further population losses for the decades to come. The most visible sign of decline are housing vacancies in different parts of the city, even of renovated stock. At the same time, the city has to cope with the consequences of hitherto shrinkage processes. Although migration balances with the hinterland recently show, in contrast to former years, a slight plus for the city, Halle has not yet been able to stabilize its population.
Keywords: 330